Activation of Ultrathin Films of Hematite for Photoelectrochemical Water Splitting via H2 Treatment. Issue 9 (4th February 2015) - Moir, Jonathon; Soheilnia, Navid; Liao, Kristine; O'Brien, Paul; Tian, Yao; Burch, Kenneth S.; Ozin, Geoffrey A.
Abstract Thermal treatment of ultrathin films of hematite (α‐Fe2O3) under an atmosphere of 5 % H2 in Ar is presented as a means of activating α‐Fe2O3 towards the photoelectrochemical splitting of water. Spin‐coated films annealed in air exhibited no photoactivity, whereas films treated in hydrogen exhibited a photocurrent response. X‐ray photoelectron spectroscopy and UV/Vis absorption spectroscopy results showed that the H2‐treated films contain oxygen vacancies, which suggests improved charge transport. However, Tafel slopes, scan‐rate dependent measurements, and kinetic analyses performed by using H2O2 as a hole scavenger suggested that surface modification may also contribute to their induced photoactivity. Electrochemical impedance spectroscopy results revealed the buildup of a surface trap capacitance at the point of photocurrent onset for the hydrogen‐treated films under illumination. A decrease in charge trapping resistance was also observed, which suggests improved transport of charges away from the surface.